Punitive Damages and the Demand for Insurance - Doherty, Neil A.; Eckles, David L. (Assurances et gestion des risques / Insurance and Risk Management, 2011)
This study examines the theoretical effects of punitive damage awards on the demand for insurance. The demand for insurance is shown to be decreasing in the amount of possible punitive damage awards. The decrease in demand occurs as a result of these awards being priced into the insurance premium. This model shows yet another reason for the existence of partial insurance even with fairly priced insurance premiums.